2020
DOI: 10.1007/s10067-020-05411-x
|View full text |Cite
|
Sign up to set email alerts
|

Living with arthritis: a “training camp” for coping with stressful events? A survey on resilience of arthritis patients following the COVID-19 pandemic

Abstract: Resilience is defined as "the capacity of individuals to cope successfully with significant change or adversity". The challenge posed by the COVID-19 pandemic may potentially represent an overwhelmingly stressful event for patients with chronic diseases. Aim of our study was to investigate the levels of resilience in individuals with inflammatory arthritis living in Emilia Romagna, the third hardest-hit Italian region during the ongoing COVID-19 pandemic. To this purpose, we developed a survey consisting of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
(34 reference statements)
2
18
1
Order By: Relevance
“…Resilience can be defined as a multidimensional structure that explains the long-term positive effects resulting from the ability to adapt to threatening or traumatic experiences [ 39 ]. Resilience is strongly negatively correlated with depression and anxiety [ 38 ]. In our study, the similarity of depression and anxiety scores between the patient and control groups of children younger than 12 years and their parents may be related to the resilience that develops adaptively to the presence of chronic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resilience can be defined as a multidimensional structure that explains the long-term positive effects resulting from the ability to adapt to threatening or traumatic experiences [ 39 ]. Resilience is strongly negatively correlated with depression and anxiety [ 38 ]. In our study, the similarity of depression and anxiety scores between the patient and control groups of children younger than 12 years and their parents may be related to the resilience that develops adaptively to the presence of chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with autoimmune diseases can develop stronger resilience as an adaptive response to the chronicity of their condition [36][37][38]. Resilience can be defined as a multidimensional structure that explains the long-term positive effects resulting from the ability to adapt to threatening or traumatic experiences [39].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is not surprising that during the COVID-19 pandemic, a 36% rate of anxiety and 31% rate of depression was recorded among lymphoma outpatients [ 10 ]. Coping styles associated with better QOL in cancer patients included emotional support and acceptance, [ 11 ] while living alone and insufficient social support seem to be associated with treatment non-adherence in patients with hematological malignancies [ 12 ] However in this respect, a recent study showed that patients with chronic conditions such as inflammatory arthritis seem to have a better capacity to successfully cope with stressful events during COVID-19 pandemic [ 13 ]. Nevertheless, this point was not truly evaluated among patients with hematological malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Various anti-rheumatic strategies, like IL-6 inhibitor (Tocilizumab) and JAK inhibitor (Baricitinib) are being investigated for COVID treatment [ 7 – 10 ]. Observational, meta-analysis and multi-omics approach-based studies indicate that the autoimmune disease group patients are at significant risk for COVID-19 infection [ 11 13 ] which calls for the inclusion of adjuvant therapies. In lieu of the above, we have reviewed here the scientific literature on vitamin D deficiency as a risk factor and its supplementation benefits in RA and COVID diseases.…”
Section: Introductionmentioning
confidence: 99%